Nonanthropocentric transvaluation of all values. On axiological grounds of nonanthropocentrisms in the selected trends of contemporary feminist philosophy - Rogowska-Stangret, Monika (Hybris, 2022)
Nonanthropocentric approaches are one of the predominant features of contemporary feminist philosophy, especially in critical posthumanities (e.g. Rosi Braidotti) and feminist new materialisms (e.g. Diana Coole). The author aims at outlining the axiological grounds of the turn to nonanthropocentrism. It is done in two steps. First, the author points to recent debates around the impossibility to separate values from facts in the mentioned contemporary trends (illustrated with reference to Bruno Latour, Donna Haraway and Karen Barad). Second, the author presents how the subject of knowledge changes together with the need to uncover the entanglement of values and facts (using the example of Haraway). The author presents responsibility (as response-ability), interdependence and care as an axiological foundation of nonanthropocentrism. The posthumanistic and nonanthropocentric critique of humanism is here presented as motivated by ethics above all other aspects.